2016
DOI: 10.1038/srep37645
|View full text |Cite
|
Sign up to set email alerts
|

Bph32, a novel gene encoding an unknown SCR domain-containing protein, confers resistance against the brown planthopper in rice

Abstract: An urgent need exists to identify more brown planthopper (Nilaparvata lugens Stål, BPH) resistance genes, which will allow the development of rice varieties with resistance to BPH to counteract the increased incidence of this pest species. Here, using bioinformatics and DNA sequencing approaches, we identified a novel BPH resistance gene, LOC_Os06g03240 (MSU LOCUS ID), from the rice variety Ptb33 in the interval between the markers RM19291 and RM8072 on the short arm of chromosome 6, where a gene for resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
148
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 62 publications
(105 reference statements)
3
148
0
1
Order By: Relevance
“…Real-time PCR analysis showed that BPH32 was expressed in all investigated tissues at the flowering stage, and its expression level was the highest in leaf sheaths followed by leaf blades, culms, and roots but not the panicle [9]. The result of our study was consistent with previous studies that showed high BPH32 expression in the leaf sheaths but a poor expression in the uppermost internode at heading stage of the same plant.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Real-time PCR analysis showed that BPH32 was expressed in all investigated tissues at the flowering stage, and its expression level was the highest in leaf sheaths followed by leaf blades, culms, and roots but not the panicle [9]. The result of our study was consistent with previous studies that showed high BPH32 expression in the leaf sheaths but a poor expression in the uppermost internode at heading stage of the same plant.…”
Section: Discussionsupporting
confidence: 83%
“…BPH32 which encloses a unique short consensus repeat domain protein and is located in the plasma membrane, has been reported to inhibit BPH feeding [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations